Brazing copper and alumina metallized with Ti-containing Sn0.3Ag0.7Cu metal powder. (15th December 2015) - Fu, W.; Song, X.G.; Hu, S.P.; Chai, J.H.; Feng, J.C.; Wang, G.D.
Abstract: A Sn-based metallization layer was successfully prepared on the surface of alumina at 900 °C by using Ti-containing Sn0.3Ag0.7Cu (SAC, wt.%) metal powder. Reliable alumina/copper joints were obtained by brazing pre-metallized alumina and copper using SAC filler at 580–660 °C for 5 min. The typical interfacial microstructure of brazed joint was copper/Cu3 Sn layer/Cu6 Sn5 layer/β-Sn layer containing Ti6 Sn5 phase and Al2 O3 particles/alumina. As brazing temperature increased, the Cu–Sn intermetallic layers thickened rapidly and the amount of β-Sn phase reduced. When brazing temperature exceeded 640 °C, Kirkendall voids and microcracks formed at copper/Cu3 Sn interface. The joints brazed at 580–620 °C possessed high shear strength and the highest average shear strength of 32 MPa was achieved when brazed at 620 °C. Fracture analyses indicated that the joints mainly fractured inside of the Cu6 Sn5 layer and β-Sn layer. The joints brazed above 620 °C demonstrated low shear strength due to the formation of Kirkendall voids which caused the joints fractured along the Cu/Cu3 Sn interface. Graphical abstract: Alumina–copper joining was successfully achieved by brazing copper and alumina metallized by Ti-containing Sn0.3Ag0.7Cu metal powders. And the brazed joints possessed high joining properties:(a) Alumina was coated by a metallization layer, consisting of β-Sn and Ti6 Sn5 .(b) Interfacial microstructure of pre-metallized alumina/copper joint; and (c) Effect of brazing temperature on the shear strength of alumina/copper joints. Highlights: Alumina was metallized by Sn0.3Ag0.7Cu–6%Ti (wt.%) at 900 °C for 30 min. Brazing of metallized alumina to copper was achieved with Sn0.3Ag0.7Cu filler. Interfacial microstructure and joint properties depended on brazing temperature. The highest shear strength of alumina/copper joint reached 32 MPa.